2020
DOI: 10.1111/1759-7714.13777
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling of Brazilian non‐small cell lung cancer patients (GBOT 0118/LACOG0418)

Abstract: Background The aim of this study was to carry out a descriptive analysis of the somatic genetic profile and co‐occurring mutations of non‐small cell lung cancer (NSCLC) samples from patients tested with comprehensive genomic profiling (CGP). Methods This was a retrospective cross‐sectional study of patients diagnosed with NSCLC from 2013 to 2018 in Brazil and whose samples were submitted to CGP (FoundationOne or FoundationACT) using either tumor or circulating tumor DNA (ctDNA) from plasma. Results We recovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
4
10
1
Order By: Relevance
“…Additionally, 4.6% patients of the tested population were positive for ALK. This is concordant with several studies worldwide [11,15]. This makes the total driver mutation rate at 17.2% (22/128).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, 4.6% patients of the tested population were positive for ALK. This is concordant with several studies worldwide [11,15]. This makes the total driver mutation rate at 17.2% (22/128).…”
Section: Discussionsupporting
confidence: 92%
“…A recently published study found an association with somatic mutations in EGFR and ERBB2 , as well as low TMB in the tumor lung samples carrying the TP53 p.R337H variant. 47 Two of eight lung tumor samples, from the present study, had TMB information, and both cases showed a low TMB (< 10 mutations/Mb). Only one case showed ERBB2 somatic mutation, and it was not associated with the presence of EGFR mutation.…”
Section: Discussionmentioning
confidence: 57%
“… 45 Lung cancer represented 29% (220 of 755) of our samples, and 3.6% (8 of 220) of the tumor lung samples carried the TP53 p.R337H variant. Mascarenhas et al 47 analyzed 513 non–small-cell lung cancer tumor genomic profiles from a Brazilian lung cancer cohort and found the TP53 p.R337H variant in the 4.3% of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the frequency of TP53 mutations in lung adenocarcinoma tumors ranges from 29% to 60%, possibly due to variations in methodology, histological subtypes, and ethnic populations [1,11,18,[20][21][22][23][24][25][26][27][28][29]. In 2014, the TCGA reported that about 45% of lung adenocarcinoma patients harbor TP53 mutations [1].…”
Section: Discussionmentioning
confidence: 99%